Apixaban and dalteparin in active malignancy‐associated venous thromboembolism: The ADAM VTE trial. (28th November 2019) - McBane, Robert D.; Wysokinski, Waldemar E.; Le‐Rademacher, Jennifer G.; Zemla, Tyler; Ashrani, Aneel; Tafur, Alfonso; Perepu, Usha; Anderson, Daniel; Gundabolu, Krishna; Kuzma, Charles; Perez Botero, Juliana; Leon Ferre, Roberto A.; et al.
Abstract: Background: Low‐molecular‐weight heparin is the guideline‐endorsed treatment for cancer‐associated venous thromboembolism (VTE). While apixaban is approved for the treatment of acute VTE, limited data support its use in cancer patients. Objectives: The primary outcome was major bleeding. Secondary outcomes included VTE recurrence and a composite of major plus clinically relevant non‐major bleeding (CRNMB). Patients/Methods: Patients with cancer‐associated VTE were randomly assigned to receive either apixaban 10 mg twice daily for seven days followed by 5 mg twice daily for six months or subcutaneous dalteparin (200 IU/kg for one month followed by 150 IU/kg once daily). Results: Of 300 patients randomized, 287 were included in the primary analysis. Metastatic disease was present in 66% of subjects; 74% were receiving concurrent chemotherapy. Major bleeding occurred in 0% of 145 patients receiving apixaban, compared with 1.4% of 142 patients receiving dalteparin [ P = .138; hazard ratio (HR) not estimable because of 0 bleeding event in apixaban group]. Recurrent VTE occurred in 0.7% of apixaban, compared to 6.3% of dalteparin patients [HR 0.099, 95% confidence interval [CI], 0.013‐0.780, P = .0281). Major bleeding or CRNMB rates were 6% for both groups. Conclusions: Oral apixaban was associated with low major bleeding and VTE recurrence rates for the treatment of VTE in cancer patients.